Downregulation of long noncoding RNA LINC00683 associated with unfavorable prognosis in prostate cancer based on TCGA. Issue 8 (8th April 2019) - Liu, Yunfeng; Yang, Bishan; Su, Youmin; Xiang, Qiuling; Li, Quhuan
Abstract: Prostate cancer (PCa) is the third most common reason of cancer‐related deaths in men. Accumulating evidence has shown that dysregulation of long noncoding RNAs (lncRNAs) is closely related to cancer initiation and development. Although large numbers of lncRNAs have been discovered, knowledge regarding their function and physiological/pathological significance remains limited. In this study, we aimed to reveal functional lncRNAs and identify prognosis‐related RNAs in PCa by analyzing data from The Cancer Genome Atlas (TCGA). To achieve this, an lncRNA‐mRNA coexpression network was constructed by weighted correlation network analysis. Additionally, a subnetwork was extracted from this weighted correlation network, and seven lncRNAs were identified as core nodes. Further Kaplan‐Meier survival analysis showed that three lncRNAs (LINC00683, LINC00857, and FENDRR) were significantly downregulated in PCa samples, and there was a strong positive correlation with patient survival. Importantly, LINC00683 has not been fully reported as related with PCa. Additionally, gene set enrichment analysis indicated that LINC00683 might be involved in cancer‐related pathways such as the Wnt pathway. Based on the findings of this study, lncRNA LINC00683 is likely to provide a new diagnostic biomarker and therapeutic target for future PCa treatments. Abstract : In this study, we fully mined existing TCGA data sets for novel factors associated with prostate cancer, and identified three lncRNAs (LINC00683, LINC00857, FENDRR) as novel potential prognostic factors. Importantly, we found lncRNA LINC00683 is most likely to be a novel diagnostic biomarker or therapeutic target, when we carried out the extensively survey of the literature and bioinformatic functional analysis for it. This interesting finding is meaningful for pathologic research and future treatment of prostate cancer.